2020
DOI: 10.1002/slct.202000063
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis and Corrosion Behaviour of Poly(o–anisidine)‐TiO2 Nanocomposite on ZnNi‐Plated Carbon Steel

Abstract: Electrosynthesis of poly(o‐anisidine) (POA) homopolymer and poly(o‐anisidine)‐TiO2 (POA‐TiO2) nanocomposite were carried out on ZnNi plated carbon steel (CS/ZnNi). The synthesis was achieved cyclic voltammetry technique in 0.2 M sodium oxalate solution containing 0.1 M o‐anisidine and o‐anisidine + 0.2 gL−1 TiO2 nanoparticles for POA and POA‐TiO2, respectively. The POA and POA‐TiO2 nanocomposite were characterized by scanning electron microscopy (SEM), energy dispersion x‐ray analysis (EDX), electrochemical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The main factors affecting the anticorrosion performance of electrodeposited coating include thickness, doping type of film, oxidation type and degree, porosity, roughness and adhesion. Numerous studies have been reported that several nanoparticles such as alumina (Al2O3) [32], titanium dioxide (TiO2) [33], silica (SiO2) [34] and nanopolymer composite [35,36] incorporated into the polymer matrix to improve the electron transfer rate, mechanical properties and corrosion resistance of coatings. Spinel ferrites (MFe2O4) which include the transition metals such as Zn, Co, Mn or Ni ions exhibit richer redox properties than single metallic oxide in electrochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The main factors affecting the anticorrosion performance of electrodeposited coating include thickness, doping type of film, oxidation type and degree, porosity, roughness and adhesion. Numerous studies have been reported that several nanoparticles such as alumina (Al2O3) [32], titanium dioxide (TiO2) [33], silica (SiO2) [34] and nanopolymer composite [35,36] incorporated into the polymer matrix to improve the electron transfer rate, mechanical properties and corrosion resistance of coatings. Spinel ferrites (MFe2O4) which include the transition metals such as Zn, Co, Mn or Ni ions exhibit richer redox properties than single metallic oxide in electrochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Batteries, artificial muscles, membranes, and corrosion technology can be given as examples for the application of the conductive polymers [15]. Conductive polymers can be synthesized via chemical [16,17] or electrochemical methods [18][19][20]. Their easy preparation, high conductivity, and stability enabled them to be used in enzyme immobilization [21].…”
Section: Introductionmentioning
confidence: 99%